Are neuroaesthetic principles applied in art therapy protocols for neurorehabilitation? A systematic mini-review - Oliva, Amelia; Iosa, Marco; Antonucci, Gabriella; De Bartolo, Daniela (Frontiers in Psychology, 2023)
Art is an instrument created by humans as an alternative way of expression. For this reason, it has found its use in clinical contexts to improve mood, increase participation in therapy, or improve communication for patients with different pathologies. In this systematic mini-review, the Preferred Reporting Item for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were adopted. Internet-based bibliographic searches were conducted via major electronic databases (Web of Science and PubMed). We analyzed the quantitative studies in which art figures as a neurorehabilitation treatment to identify whether standard art therapy protocols exist and whether these are based on the principles of neuroaesthetics. Our review identified 8 quantitative and 18 qualitative studies. Although art therapy has been used for more than 20 years as a clinical tool, there are no standard protocols to refer to when planning interventions. Although the effectiveness of using arts as therapy has been reported in many qualitative or feasibility studies, there is still a lack of quantitative studies in which the outcomes of art therapy are directly based on the principles of neuroaesthetics.